Strategi Pendidikan Toleransi Beragama dan Implikasinya terhadap Keutuhan NKRI di Bangka Belitung (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
This article aims to review and describe the strategy of religious tolerance education and its impact on the integrity of the Negara Kesatuan Republik Indonesia (NKRI) in Bangka Belitung. In the Bangka Belitung Islands, the life of the people is very heterogeneous and has a high level of plurality. There are many portraits of the diversity of ethnicities, cultures, religions, ethnicities and languages ​​that are integrated into the social dynamics of the people in Bangka Belitung. Of course, this plurality has the potential to cause horizontal conflict in society. Therefore, to study and examine in depth this reality an in-depth interview technique is used to obtain clear information about the principles of religious tolerance from the perspective of Islam, Christianity, Buddhism, Hinduism, and Confucianism. As a result, there are three educational strategies that can be developed by religious communities in Bangka Belitung; first, the strategy of educating the internal religious community; second, the strategy of educating people to maintain harmony between fellow religious communities; and third, the strategy of educating people to maintain harmony with the government.Artikel ini bertujuan untuk mengulas dan memaparkan strategi pendidikan toleransi beragama dan dampaknya terhadap keutuhan Negara Kesatuan Republik Indonesia (NKRI) di Bangka Belitung. Di Kepulauan Bangka Belitung kehidupan masyarakatnya sangat heterogen dan memiliki tingkat pluralitas yang tinggi. Ada banyak potret keragaman suku, budaya, agama, etnis, dan bahasa yang  menyatu dalam dinamika sosial masyarakat di Bangka Belitung. Tentu, pluralitas tersebut berpotensi menimbulkan konflik horizontal di tengah masyarakat. Oleh karena itu untuk mengkaji dan menelaah secara mendalam realitas tersebut digunakan teknik wawancara mendalam untuk mendapatkan informasi yang jelas mengenai prinsip toleransi beragama dalam perspektif agama Islam, Kristen, Budha, Hindu, dan Konghucu. Hasilnya, ada tiga strategi pendidikan yang dapat dikembangkan oleh umat beragama yang ada di Bangka Belitung; pertama, strategi mendidik dalam internal umat beragama; kedua, strategi mendidik umat untuk menjaga kerukunan antara sesama umat beragama; dan ketiga, strategi mendidik umat untuk menjaga kerukuan dengan pemerintah.